지역아동센터 저소득층 아동의 차별피해 영향요인 분석 - 우정자(Jung-Ja Woo) (한국콘텐츠학회 논문지, 21(12), 2021)
The purpose of this study is to investigate the factors that affect the discrimination of low-income children among children in the community children's centers. The subjects of the survey were 6th grade elementary school students who were the third respondents of the second Child Panel Survey of the community children's center, among them, 355 children whose family economy level corresponds to basic living allowance, next level, and blind spot. SPSS Statistics 25.0 was used to analyze exploratory factors, reliability analysis, frequency analysis, descriptive statistics, correlation analysis, and multiple regression analysis. The results of this study showed that single parent family, parent social capital, parental abuse, and happiness had a significant effect on the discrimination damage of low-income children in community children's centers. The more one parent's family, the less the parent's role as a counterpart to the discussion, and the more the parental abuse, the higher the child's discrimination damage. In general, parents-related factors were affecting the discrimination damage of low-income children. Community children's centers and related institutions should focus on developing and implementing programs that can improve the quality of family relations of children. 본 연구는 지역아동센터 이용 아동 중에서 저소득층 아동의 차별피해에 영향을 미치는 요인을 알아보고자 하는 목적을 가지고 있다. 조사의 대상은 지역아동센터 아동패널조사 2기 3차의 응답자인 초등학교 6학년생이며, 이중에서 가정경제 수준이 기초생활수급대상, 차상위, 사각지대에 해당하는 아동 355명이다. SPSS Statistics 25.0을 이용하여 탐색적 요인분석, 신뢰도분석, 빈도분석, 기술통계, 상관관계분석, 다중회귀분석방법을 사용하였다. 연구결과, 한부모 가정, 부모 의논상대 존재 여부, 부모의 학대, 행복감이 지역아동센터 저소득층 아동의 차별피해에 유의미한 영향을 미치는 것으로 나타났다. 한부모 가정일수록, 부모가 의논상대 역할을 하지 못할수록, 부모 양육태도가 학대의 경향일수록 아동의 차별피해는 높아지는 것으로 나타났다. 대체로 부모 관련 요인들이 저소득층 아동의 차별피해에 영향을 미치고 있었다. 지역아동센터 및 관련 기관들은 이용 아동의 가족관계의 질을 향상시킬 수 있는 프로그램 개발과 실행에 역점을 두어야 한다.